EFFECTIVE METHODS OF DEVELOPING PHYSICAL QUALITIES OF PRIMARY SCHOOL STUDENTS THROUGH ACTIVE GAMES (Scientific journal of the Fergana State University, 2026)
The article analyzes the role of active games in the development of physical qualities in primary school students, their pedagogical and physiological foundations, as well as ways to integrate game-based technologies into the educational process. The study scientifically substantiates the effectiveness of active games in developing children’s speed, endurance, agility, and balance. In addition, the content of the latest decrees and orders of the President of the Republic of Uzbekistan in the field of physical education and sports is analyzed, highlighting the urgent tasks of promoting a healthy lifestyle within the primary education system.